QOL-47. ApoE4 AS A GENETIC PREDICTOR FOR NEUROCOGNITIVE OUTCOMES IN PEDIATRIC BRAIN TUMOR SURVIVORS. Issue 2 (22nd June 2018) - Kline, Cassie; Felton, Erin; Byer, Lennox; Stoller, Schuyler; Torkildson, Joseph; Gauvain, Karen; Samuel, David; Tong, Elizabeth; Liu, John; Fullerton, Heather; Dubal, Dena; Mueller, Sabine
Abstract: Long-term neurocognitive deficits in pediatric brain tumor survivors are challenging to both predict and treat. In a previous cohort analysis, we identified the genetic variant for ApoE4 reliably correlates with decreased neurocognitive function over time. Herein, we present case-control analyses comparing neurocognitive outcomes of ApoE4 carriers versus non-carriers in a group of pediatric brain tumor survivors. Utilizing an existing cohort of pediatric brain tumor patients from a diverse population, we isolated cases heterozygous for ApoE4 and matched these to controls carrying ApoE3. Priority was placed on matching cases and controls along variables previously identified to impact neurocognition – time from radiation and hydrocephalus or seizures at diagnosis. Student t-tests and lowess smoothing regression were used to compare outcomes in 6 neurocognitive domains over multiple time points. Twenty matched cases and controls were included in the analyses. At baseline, there were no statistically significant differences between cases and controls in any domain. Over time, ApoE3 controls performed statistically significantly higher across an increasing number of neurocognitive domains than ApoE4 carriers. Using smoothing regression, cases visibly performed worse over time as compared to controls and as seen by decreasing neurocognitive scores across all domains. ApoE4 carrier status strongly correlates with neurocognition function over time in pediatric brain tumor survivors. This effect appears across multiple domains and may show evidence of progressive deterioration with each year from treatment. Our results identify ApoE4 as a possible genetic predictor for neurocognitive outcomes in pediatric brain tumor survivors and support further investigation of this genetic variant.